Infectious Diseases Seen in a Primary Care Clinic in Leogane, Haiti - Neuberger, Ami (The American Society of Tropical Medicine and Hygiene, 2012)
All diseases diagnosed in a primary healthcare clinic situated in Leogane, Haiti, were recorded prospectively during a 7-month period. Among the patients in this cohort, 2,821 of 6,631 (42.6%) presented with an infectious disease. The three most common syndromes among the patients presenting with infections were respiratory tract infections (33.5%), suspected sexually transmitted diseases—mostly among females with recurrent disease (18.1%)—and skin and soft tissue infections, including multiple cases of tinea capitis (12.8%). Of the 255 patients presenting with undifferentiated fever, 76 (29.8%) were diagnosed with falciparum malaria. Other vector-borne diseases included 13 cases of filariasis and 6 cases of dengue fever. Human immunodeficiency virus infection was diagnosed in 19 patients. Four cases of mumps were detected among unimmunized children. A large proportion of these infections are preventable. Concerted efforts should be made to create large-scale preventive medicine programs for various infectious diseases.